A bird pollinator shows positive frequency dependence and constancy of species choice in natural plant communities. Issue 11 (3rd November 2016) - Schmid, B.; Nottebrock, H.; Esler, K. J.; Pagel, J.; Böhning‐Gaese, K.; Schurr, F. M.; Mueller, T.; Schleuning, M.
Abstract: Animal pollinators mediate reproduction of many plant species. Foraging theory suggests that animal pollinators exhibit preferences for common plant species in natural communities (positive frequency‐dependent foraging) and temporary single‐species specialization (flower constancy) during foraging bouts. Positive frequency dependence may favor common plant species; flower constancy may enhance conspecific pollen transfer particularly in rare plant species. Previous experimental studies suggest that avian pollinators are unlikely to exhibit these behaviors. We studied foraging behavior of Cape Sugarbirds ( Promerops cafer ), the main avian pollinator of many Protea species, using focal‐plant and focal‐bird sampling, assisted by high‐resolution maps of the spatiotemporal distribution of Protea individuals and their flowering status. We found that Sugarbird's visitation preference increased with species' relative floral abundance, and that individual Sugarbirds tended to visit single species in sequence. Flower constancy during foraging bouts was significantly higher than expected from random plant–animal encounters at the scale of pollinator movements. Positive frequency dependence may favor the reproduction of abundant plant species while flower constancy may be particularly important for rare plant species. This first simultaneous study of both behaviors in a natural plant–pollinator system shows that bird pollinators exhibit both types of behavior and, in this way, possibly influence plant community structure.